The effects of spent mushroom compost on plant growth performance and soil properties on Amaranthus tricolor - Jaludin, Nabilah; Rusli, Lili Syahani (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Spent mushroom composts (SMC) are agricultural wastes from harvested mushroom farms. In Malaysia alone over 100 tonnes of fresh mushrooms are produced. Annually resulting in 438 tonnes of composted leftovers that require disposal. Currently, only 28% of the SMC is recycled for agricultural use, while 3% was burned, and over 69% is dumped in landfills or on the ground. However, it has been proven that SMC, which is rich in nutrients and organic materials, is an excellent option for agriculture as it is ideal for mulching soil and enhancing nutrient content. Thus, the objective of this study is to determine the effects of SMC on Amaranthus tricolor growth performance and to investigate its impact on soil properties. In this research, various concentrations of SMC 10%,20%,30% and 50% were applied to A. tricolor plants to evaluate their impact on plant height, leaf area, number of nodes and internodes, and stem diameter. Concurrently, soil samples were analyzed to determine the changes in soil analysis and proximate analysis. The results indicated that the applications of SMC significantly enhanced the growth performance of A. tricolor. From all of the treatments with SMC, the result obtained from the growth analysis of A. tricolor showed that the vegetable planted on 20% of SMC soil had the best growth. Overall, this study demonstrates that a certain amount of SMC on to soil is necessary to be an effective organic amendment for improving the growth of A. tricolor and enhancing soil health.